Hohn C. White, Digest of the Laws and Ordinances of the Parish of East Feliciana 80 (1847) - (:unkn) unknown (My University, 1848)
Prohibited discharge of arms within the limits of the town Clinton, except in extreme circumstances. Punishable by fine.
Keywords: DISCHARGE